Urinary Incontinence as a Predictor of Death: A Systematic Review and Meta-Analysis. - Gregor John; Claire Bardini; Christophe Combescure; Patrick Dällenbach (PLoS ONE)
Background The association between urinary incontinence (UI) and increased mortality remains controversial. The objective of our study was to evaluate if this association exists. Methods We performed a systematic review and meta-analysis of observational studies comparing death rates among patients suffering from UI to those without incontinence. We searched in Medline, Embase and the Cochrane library using specific keywords. Studies exploring the post-stroke period were excluded. Hazard ratios (HR) were pooled using models with random effects. We stratified UI by gender and by UI severity and pooled all models with adjustment for confounding variables. Results Thirty-eight studies were retrieved. When compared to non-urinary incontinent participants, UI was associated with an increase in mortality with pooled non adjusted HR of 2.22 (95%CI 1.77-2.78). The risk increased with UI severity: 1.24 (95%CI: 0.79-1.97) for light, 1.71 (95%CI: 1.26-2.31) for moderate, and 2.72 (95%CI: 1.90-3.87) for severe UI respectively. When pooling adjusted measures of association, the resulting HR was 1.27 (95%CI: 1.13-1.42) and increased progressively for light, moderate and severe UI: 1.07 (95%CI: 0.79-1.44), 1.25 (95%CI: 0.99-1.58), and 1.47 (95%CI: 1.03-2.10) respectively. There was no difference between genders. Conclusion UI is a predictor of higher mortality in the general and particularly in the geriatric population. The association increases with the severity of UI and persists when pooling models adjusted for confounders. It is unclear if this association is causative or just reflects an impaired general health condition. As in most meta-analyses of observational studies, methodological issues should be considered when interpreting results.